Nurse-Delivered Brief Behavioral Treatment for Insomnia in Lung Cancer Survivors: A Pilot RCT. Issue 6 (1st November 2020) - Dean, Grace E.; Weiss, Carleara; Jungquist, Carla R.; Klimpt, Michelle L.; Alameri, Rana; Ziegler, Patricia A.; Steinbrenner, Lynn M.; Dexter, Elisabeth U.; Dhillon, Samjot S.; Lucke, Joseph F.; Dickerson, Suzanne S.
ABSTRACT: Objective/Background : Insomnia occurs in 50 to 80% of lung cancer survivors. Cognitive behavioral therapy is the standard treatment for insomnia (CBTI); however, treatment length and lack of psychologists trained in CBTI limits access. Brief Behavioral Treatment for Insomnia (BBTI), a nurse-delivered modified CBTI, is proposed. This feasibility pilot study sought to compare the BBTI intervention to attention control Healthy Eating Program (HEP) for insomnia in lung cancer survivors. Participants : The participants comprised adults, 21 years of age or older with insomnia and stage I/II non-small cell lung cancer, more than 6 weeks from surgery and living in Western NY. Methods : Participants (n = 40) were randomly assigned to an experimental (BBTI) or attention control condition (Healthy Eating Program). Thirty participants completed the study. Results : Participants were 66 years of age (± 7.6; range 53–82), 40% (n = 16) male, 87.5% (n = 35) Caucasian, 50% (n = 20) married, BMI 27.7 (± 5.8), and 12% (n = 5) never smokers. Baseline sleep diary sleep efficiency, ISI and other baseline covariates were balanced between the groups. Sleep efficiency improved ≥85% in BBTI group ( p = .02), but not in HEP control group ( p = 1.00). Mean ISI for BBTI and attention control were 6.40 ± 4.98 and 14.10 ± 4.48 ( p = .001) respectively. In addition, BBTI group mean total FACT-L score improved by 6.66 points from baseline while HEP group score worsened ( p = .049). Conclusions : BBTI is a practical, evidence-based, clinically relevant intervention that improved sleep and quality of life in lung cancer survivors with insomnia. Additional research to evaluate efficacy, duration, and implementation strategies are essential.